Volatile Constituents of Some Selected Plant Species Traditionally Used as Tea in the Sharri Mountains (Kosovo) - Avni Hajdari; Nita Kelmendi; Genista Mustafa; Behxhet Mustafa; Dashnor Nebija (The Scientific World Journal)
The study evaluates the chemical composition of the volatile constituents of ten plant species traditionally used as herbal tea in the Sharri Mountain regions (Kosovo and North Macedonia). Volatile constituents responsible for the flavour and fragrance of selected species (Crataegus monogyna, Cydonia oblonga, Malus sylvestris, Matricaria chamomilla, Morus alba, Morus nigra, Rosa canina, Sambucus nigra, Tilia cordata, and Vaccinium myrtillus) were separated and then identified using GC-MS, whereas GC-FID is employed for the quantitative analysis. Experimental data revealed different patterns of volatile constituents depending on plant species. Monoterpenes, sesquiterpenes, diterpenes, and norisoprenoids were the most abundant volatile constituents. Principal component analysis (PCA) was deployed for data analysis and resulted in grouping these ten species in four principal clusters. The combination of various volatile constituents present in specific plant species may play an important role in the specific aroma and taste sensation of these species used as recreational teas.